RNA Interference of Trypanosoma brucei Cathepsin B and L Affects Disease Progression in a Mouse Model - Abdulla, Maha-Hamadien; O'Brien, Theresa; Mackey, Zachary B.; Sajid, Mohamed; Grab, Dennis J.; McKerrow, James H. (PLOS Neglected Tropical Diseases, 2008)
We investigated the roles played by the cysteine proteases cathepsin B and cathepsin L (brucipain) in the pathogenesis of Trypansoma brucei brucei in both an in vivo mouse model and an in vitro model of the blood–brain barrier. Doxycycline induction of RNAi targeting cathepsin B led to parasite clearance from the bloodstream and prevent a lethal infection in the mice. In contrast, all mice infected with T. brucei containing the uninduced Trypanosoma brucei cathepsin B (TbCatB) RNA construct died by day 13. Induction of RNAi against brucipain did not cure mice from infection; however, 50% of these mice survived 60 days longer than uninduced controls. The ability of T. b. brucei to cross an in vitro model of the human blood–brain barrier was also reduced by brucipain RNAi induction. Taken together, the data suggest that while TbCatB is the more likely target for the development of new chemotherapy, a possible role for brucipain is in facilitating parasite entry into the brain.